Extent of tumor fibrosis/hyalinization and infarction following neoadjuvant radiation therapy is associated with improved survival in patients with soft‐tissue sarcoma. (27th November 2021) - Rao, Sneha R.; Lazarides, Alexander L.; Leckey, Bruce L.; Lane, Whitney O.; Visgauss, Julia D.; Somarelli, Jason A.; Kirsch, David G.; Larrier, Nicole A.; Brigman, Brian E.; Blazer, Dan G.; Cardona, Diana M.; Eward, William C.
Abstract: Introduction: Current standard of care for most intermediate and high‐grade soft‐tissue sarcomas (STS) includes limb‐preserving surgical resection with either neoadjuvant radiation therapy (NRT) or adjuvant radiation therapy. To date, there have been a few studies that attempt to correlate histopathologic response to NRT with oncologic outcomes in patients with STS. Methods: Using our institutional database, we identified 58 patients who received NRT followed by surgical resection for primary intermediate or high‐grade STS and 34 patients who received surgical resection without NRT but did receive adjuvant radiation therapy or did not receive any radiation therapy. We analyzed four histologic parameters of response to therapy: residual viable tumor, fibrosis/hyalinization, necrosis, and infarction (each ratiometrically determined). Data were stratified into two binary groups. Unadjusted, 5‐ and 10‐year overall survival, and relapsed‐free survival (RFS) were calculated using the Kaplan–Meier method. Results: Analysis of pathologic characteristics showed that patients treated with NRT demonstrate significantly higher tumor infarction, higher tumor fibrosis/hyalinization, and a lower percent viable tumor compared with patients not treated with NRT ( p  < 0.0001). Based on Kaplan–Meier curve analysis and multivariate cox proportional hazard model for OS and RFS, patients treated with NRT and showing >12.5% tumor fibrosis/hyalinization have significantly higher overall survival and recurrence‐free survival at 5 and 10 years. Discussion and Conclusion: We have identified three histopathologic characteristics—fibrosis, hyalinization, and infarction—that may serve as predictive biomarkers of response to NRT for STS patients. Future prospective studies will be needed to confirm this association. Abstract : For patients treated with soft‐tissue sarcoma and neoadjuvant therapy, we have identified pathologic markers found at the time of surgical resection which are unique to tumors treated with NRT. Among these markers, higher percent fibrosis/hyalinization and lower percent tumor infarction were associated with improved overall survival and disease‐free survival.